Zakat Distribution and Maternal Health Improvement: An Empirical Analysis of Low Income Beneficiaries - Eka Octavian Pranata; Bunga Mar’atush Shalihah; Hanifah Hanifah; Yulia Intan Fatriana (Journal of Maternal and Child Health Sciences (JMCHS), 2026)
Maternal health disparities persist among low-income populations, where financial constraints limit access to antenatal and delivery services. Although zakat is recognized as an Islamic redistributive mechanism for poverty alleviation, its role in improving maternal health remains underexplored. This study examines the influence of zakat distribution on access to maternal healthcare services among low-income beneficiaries. Using a qualitative approach, data were collected through 23 in-depth interviews, focus group discussions, and key informant interviews involving zakat administrators and healthcare providers. Thematic analysis was conducted using the Social Determinants of Health framework to explore underlying economic and psychosocial mechanisms.The findings indicate that zakat enhances maternal health through three primary pathways: reducing financial barriers to antenatal care and institutional delivery, improving maternal nutrition during pregnancy, and alleviating economic stress. Most participants reported increased antenatal visits and better preparedness for childbirth after receiving zakat assistance. However, its impact remains limited due to the lack of structured integration between zakat institutions and formal healthcare systems. These findings suggest that zakat has the potential to function as a complementary health financing mechanism to support maternal health among vulnerable populations.